Предмет: Алгебра,
автор: skitls0295
p(x)=p1(x)+p2(x)
если p1(x)=3x в квадрате + 2x-1
p2(x)=x в кубе -3x в квадрате
Ответы
Автор ответа:
0
p(x)=p1(x)+p2(x)
p(x)=3x^2+2x-1+x^3-3x^2=x^3+2x-1; (скобки не ставим , потому что сумма многочленов
p(x)=3x^2+2x-1+x^3-3x^2=x^3+2x-1; (скобки не ставим , потому что сумма многочленов
Похожие вопросы
Предмет: Математика,
автор: elinaradcenko0
Предмет: Геометрия,
автор: KiryaJey
Предмет: Русский язык,
автор: ivanovairina60961
Предмет: Математика,
автор: polina11111111